The effects of nodes and resin on the mechanical properties of laminated bamboo timber produced from Gigantochloa scortechinii. (15th February 2016) - Anokye, Rogerson; Bakar, Edi Suhaimi; Ratnasingam, Jegatheswaran; Yong, Adrian Choo Cheng; Bakar, Nova Noliza
Highlights: Flexural performance of laminated bamboo timber with nodes improves with increase in node intervals. Weakness in node are attributed to low density and the irregular vascular bundle arrangements. Phenol formaldehyde provides higher performance than polyvinyl acetate in the LBT bonding. Glue type and spread rate have utmost influence on the compression and shear bond strengths of the LBT. Abstract: The objective of this work was to evaluate the mechanical properties of laminated bamboo timber (LBT) manufactured from bamboo ( Gigantochloa scortechinii ). Bamboo strips containing nodes were used to produce laminated samples. Each bamboo mat was arranged with 5 cm intervals ranging from 0 cm to 15 cm between the nodes in successive laminae. Phenol formaldehyde (PF) and polyvinyl acetate (PVAc) were used at two spread rates of 200 g/m 2 and 250 g/m 2 . The best mechanical properties were found in samples without nodes. Increasing intervals also resulted in increasing strengths. In all the mechanical properties studied, PF had higher strength with 200 g/m 2 spread rate except for shear where PVAc had similar values with PF. It appears that interval levels in the joints influenced the overall mechanical properties of the samples.